Spatial Analysis and Identification of Erosion and Sediment Hot-Spots Along Zagros Forest Roads - S. Yousefi; S.N. Emami; M. Nekooeimehr; S. Mardanian (علوم آب و خاک)
In the present study, the Road Sediment Delivery Model (SEDMODL) and Geographic Information System (GIS) were utilized to estimate the average annual sedimentation caused by the forest road network in the oak forests in the west of Iran, Chaharmahal and Bakhtiari Provinces (Nazi forest road with a length of 5171 meters). Sedimentation from the study forest road network was estimated based on three basic factors in the model. Also, 30 erosion benchmarks were installed to measure the erosion and sedimentation rate at different distances from the road and in different parts of the study road and changes were measured during a year. The results showed that the average soil erosion at different distances from the Nazi road based on erosion benchmarks is 5.7 mm per year. In addition, the estimated erosion and sedimentation rate of the entire study road network based on the SEDMODL model is 2875 and 570 tons per year per kilometer, respectively. Model evaluation using erosion benchmarks showed that SEDMODL is a suitable model for estimating soil erosion on forest roads in the west of Iran (R2=0.78 and RMSE=0.73). It should be noted that statistical analysis of erosion hot-spot analysis showed that 39 percent of forest roads in Nazi showed very high erosion. Based on the results of the present study, it is suggested that conservative, protective, and road maintenance measures in areas with high erosion risk should be prioritized by decision-makers.